Ultrasound-assisted extraction of antioxidants from Melastoma malabathricum Linn.: modeling and optimization using Box–Behnken design - Hosni, Suzziyana; Gani, Siti Salwa Abd; Orsat, Valérie; Hassan, Masriana; Abdullah, Sumaiyah (MDPI, 2023)
This study presents modeling and optimization of ultrasound-assisted extraction (UAE) of Melastoma malabathricum with the objective of evaluating its phytochemical properties. This one-factor-at-a-time (OFAT) procedure was conducted to screen for optimization variables whose domains included extraction temperature (XET), ultrasonic time (XUT), solvent concentration (XSC), and sample-to-liquid ratio (XSLR). Response surface methodology (RSM) coupled with Box–Behnken design (BBD) was applied to establish optimum conditions for maximum antioxidant extraction. Modeling and optimization conditions of UAE at 37 kHz, XET 32 °C for XUT 16 min and dissolved in an XSC 70% ethanol concentration at a XSLR 1:10 ratio yielded scavenging effects on 2,2-diphenyl-1-picryl-hydrazyl (DPPH) at 96% ± 1.48 and recorded values of total phenolic content (TPC) and total flavonoid content (TFC) at 803.456 ± 32.48 mg GAE (gallic acid equivalents)/g, and 102.972 ± 2.51 mg QE (quercetin equivalents)/g, respectively. The presence of high flavonoid compounds was verified using TWIMS-QTOFMS. Chromatic evaluation of phytochemicals using gas chromatography–mass spectrometry (GC–MS) revealed the presence of 14 phytocompounds widely documented to play significant roles in human health. This study provides a comparative evaluation with other studies and may be used for validation of the species’ potential for its much-acclaimed medicinal and cosmeceutical uses.